The Relationship Between the Self-Concept of Digital Immigrant Entrepreneurs in Bali and Tri Hita Karana - Dananjaya, I Kadek Arya; Pamungkas, Indra Novianto Adibayu (Eduvest - Journal of Universal Studies, 2025)
This study explores the relationship between the self-concept of digital immigrant small business owners in Bali and the Tri Hita Karana philosophy, examining how their self-concept influences their adaptation to modern business demands. The purpose of the research is to understand how digital immigrant entrepreneurs in Bali, primarily from Generation X, navigate the digital economy while maintaining cultural values rooted in Tri Hita Karana. A qualitative research method with an interpretive approach was used, involving face-to-face interviews with 30 digital immigrant small business owners in Bali. Data were analyzed using NVIVO software, which facilitated the coding and identification of themes. The results show that the self-concept of these entrepreneurs is strongly aligned with Tri Hita Karana principles, including goodwill, openness, and realism. The study also found that the entrepreneurs’ self-concept significantly influences their ability to balance modern business practices with cultural traditions. The implications of this study suggest that digital immigrants can successfully adopt modern business strategies while preserving their cultural values, and that integrating self-concept with Tri Hita Karana can lead to more harmonious business practices. This research contributes to the understanding of digital immigrants’ adaptation processes and provides insights into how cultural values can guide successful entrepreneurship in the digital age.